Project Based Learning Improves Elementary Science Cognitive Achievement: Pembelajaran Berbasis Proyek Meningkatkan Prestasi Kognitif Ilmu Pengetahuan Alam pada Tingkat Sekolah Dasar - Halimatus Sadafiyah Widiarto; Noly Shofiyah (Academia Open, 2025)
General Background: Cognitive learning outcomes in elementary science are a key indicator of educational success and students’ conceptual understanding. Specific Background: In many classrooms, science instruction still relies on conventional teacher-centered approaches, resulting in passive participation, low motivation, and superficial comprehension, particularly in abstract topics such as energy transformation. Knowledge Gap: Empirical evidence from controlled classroom implementation regarding how project-based approaches relate to measurable cognitive outcomes in elementary science contexts remains limited. Aims: This study aims to determine the effect of the Project Based Learning (PjBL) model on fourth-grade students’ cognitive learning outcomes in science. Results: Using a quantitative pre-experimental one-group pretest–posttest design with 27 students, the mean score increased from 78 to 88 after treatment, surpassing the minimum competency criterion of 75; paired t-test analysis showed statistical significance (p = 0.001; t = 8.832 > 2.045). Students also demonstrated high enthusiasm and active participation during project activities. Novelty: The study provides classroom-based empirical evidence linking PjBL implementation to measurable gains in cognitive achievement on the topic of energy transformation in an Indonesian elementary school setting. Implications: The findings support the use of project-centered inquiry as an instructional alternative to conventional methods for improving science learning outcomes and fostering meaningful learning experiences at the primary level. Highlights: Mean test performance rose from pre-instruction to post-instruction levels above the competency threshold. Statistical testing confirmed a significant difference between initial and final measurements. Learners displayed strong engagement and active involvement during project activities. Keywords: Project Based Learning; Cognitive Learning Outcomes; Elementary Science Education; Energy Transformation; Pre-Experimental Study